Coupling of subcritical methanol with acidic ionic liquids for the acidity reduction of naphthenic acids - Zafar, F. (De Gruyter Open Ltd, 2017)
The presence of naphthenic acids (NAs) in crude oil is the major cause of corrosion in the refineries and its processing equipment. The goal of this study is to reduce the total acid number (TAN) of NAs by treating them with subcritical methanol in the presence of acidic ionic liquid (AIL) catalysts. Experiments were carried out in an autoclave batch reactor and the effect of different reaction parameters was investigated. It was observed that TAN reduction was positively dependent on the temperature and concentration of the AIL whereas excess of methanol has a negative effect. Approximately 90 TAN reduction was achieved under the optimized reaction conditions using BMIMHSO4 as catalyst. It was also perceived from the experimental results that the AILs with longer alkyl chain exhibited higher catalytic activity. The activity and stability of AIL showed that they can be promising catalyst to esterify NAs under subcritical methanol. © 2017 Faisal Zafar et al., published by De Gruyter Open.